Agent Narc Is Not Your Client: Reflections on the Proper Understanding of the Relationship between Prosecutors and Investigating Agencies - Leonetti, Carrie (2017)
Assistant United States Attorneys increasingly conceive federal lawenforcement agents as their clients in criminal prosecutions. As both a descriptive and normative matter, this cannot be right. As a descriptive matter, official interpretations by the Department of Justice, the bench, the bar, and academic commentators almost always reject this client conception. It is inconsistent with the conception of prosecutorial obligations espoused by Brady v. Maryland, the American Bar Association model rules of ethics, federal statutes, and evidentiary law. As a normative matter, it could have serious implications for the law of attorney malpractice, prosecutorial immunity, the disclosure of favorable evidence to the defense, the fair adjudication of suppression hearings, the exercise of prosecutorial charging discretion, and the prevention of official misconduct